Sequential coupling of dry and wet COVID-19 screening to reduce the number of quarantined individuals. (May 2022) - Po (Harvey) Chin, Yen; Song, Wenyu; Islam, Md Mohaimenul; Bates, David W.; Zhou, Li; Chuan (Jack) Li, Yu
Highlight: This viewpoint article discusses the potential benefits of sequential coupling of digital checker (Dry screening) and Rapid Antigen Test (Wet screening) at a population level for COVID-19 positive test to reduce the number of people who require quarantine and alleviating stress on the overburdened healthcare systems during the COVID-19 pandemic. We concluded that sequential coupling of a digital checker and a Rapid Antigen Test could significantly reduce the number quarantined by around 1 million in a hypothetical country with 10 million people. Abstract: Introduction: Currently, several countries are facing severe public health and policy challenges when designing their COVID-19 screening strategy. A quantitative analysis of the potential impact that combing the Rapid Antigen Test (RAT; Wet screening) and digital checker (Dry screening) can have on the healthcare system is lacking. Method: We created a hypothetical COVID-19 cohort for the analysis. The population size was set as 10 million with three levels of disease prevalence (10%, 1%, or 0.1%) under the assumption that a positive test result will lead to quarantine. A digital checker and two RATs are used for analysis. We further hypothesized two scenarios: RAT only and RAT plus digital checker. We then calculated the number of quarantined in both scenarios and compared the two to understand the benefits of sequential coupling of a digital checker with a RAT. Result: Sequential coupling of the digital checker and RAT can significantly reduce the number of individuals quarantined to 0.95-1.33M, 0.86-1.29M, and 0.86-1.29M, respectively, under the three different prevalence levels. Conclusion: Sequential coupling of digital checker and RAT at a population level for COVID-19 positive test to reduce the number of people who require quarantine and alleviating stress on the overburdened healthcare systems during the COVID-19 pandemic.